KAJIAN AL-QURAN DI INDONESIA: Telaah Historis - Cholid Ma’arif (QOF, 2017)
This paper focuses on a mapping study of the development of Qur’anic and interpretation study generally in Indonesia. It aims to see how far the map of development of the Qur’an Study in the region of Indonesia. Previously, it is important to trace the beginning of the historical entry of Islam, the pattern and system of teaching the Koran, along with its development by looking at the work of commentary scholars and commentary on the interpretation of scholars. The method used is bibliography with supported documentation of related works. The results are the study of the Qur’an in Indonesia from classical to contemporary times evolved from the conventional pattern of the class (learning al-Qur’an in pesantren, madrasah, and home), a ceremonial event and even in competition (model reading al-Qur ‘ in various events such as One Day One Juz, STQ, MTQ, and others). On the other hand, the growth of interpretation and translation of the Koran in Indonesia is somewhat slower than the writing of interpretations in the Middle East. In this case the author traced the period of history of writing al-Qur’an interpretation according to Nasharuddin Baidan: Classic Period (7-8 H./15 CE); The Middle Period (16-18 AD); PreModern Period (19th Century); The Modern Period (The 20th Century (1900-1950, 1951-1980, 19812000, 2001-present) At first glance, it appears that at first the interpretation became an integral part with other religious teachings propagated by the wali songo (such as the teachings of Molimo and also Lir Ilir) .Then began writing the interpretation with Arabic script in the local language (ex melayu, madura). The work that appears like Tafsir Tarjuman Al-Mustafid.In this period style of writing interpretation is still influenced from the interpretation of Arab lands, such as Jalalain, al-Baidlawi, etc. The modern period is a period of Indonesian interpretation, not only of tahlili but also maudlu’I (thematic themes). The themes are carried on are social, political, economic, gender, ecological, multicultural , and others.